WONDERFUL MALANG WITH SUMMER TOUR ON SAHID MONTANA HOTEL - Patrick Citra Limanto; Aldo Soenaidy; Thiyada Wareerit; Jingru Hu; Annelieke Michelle van Engelenhoven (International Journal of Applied Business and International Management, 2017)
Hotel Sahid Montana is a 3 stars hotel. The hotel has facilities and resources that ready to go international. Team 07 knew about it, because team 07 had conducted several surveys about it. First, we search for information through Internet media. The information we get is about the facilities, prices and services that available on the official website of Sahid Montana. In addition, Team 07 also found information about consumer experiences or feedback when staying at Hotel Sahid Montana. Not only positive feedback, but also a negative feedback given by consumers. We conducted an interview with Mr. Umar as marketing manager at Hotel Sahid Montana. He explains in detail about facilities, resources, services, how to advertise, and how to handle complaints from consumers. So Team 07 made the decision that this Hotel Sahid Montana was ready for go international, although there are still some things that need to be improved for the future.This research aims to introduce Indonesian culture and increase the value of tourism object. For the hotel, to introduce and increasing value of hotel Sahid in international are.